2021
DOI: 10.3390/ijerph18189700
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Sport in Cold Environments: Practical Recommendations to Improve Sport Performance and Reduce Negative Health Outcomes

Abstract: Although not a barrier to perform sport, cold weather environments (low ambient temperature, high wind speeds, and increased precipitation, i.e., rain/water/snow) may influence sport performance. Despite the obvious requirement for practical recommendations and guidelines to better facilitate training and competition in such cold environments, the current scientific evidence-base is lacking. Nonetheless, this review summarizes the current available knowledge specifically related to the physiological impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 155 publications
1
11
0
1
Order By: Relevance
“…While the knee is the most injured body part in snowsports, with ACL ruptures as the most common type of injury,11 26 27 it has been suggested that increased muscle temperature and the resulting increase in muscle activation may be preventative, as ACL injuries occur during the first 50 ms of early impact 25 27 28. As cold ambient temperatures are known to significantly decrease muscle temperature and the rate of force development,29 a combination of active and passive methods is recommended for athletes performing at subzero temperatures 1 8 30…”
Section: Discussionmentioning
confidence: 99%
“…While the knee is the most injured body part in snowsports, with ACL ruptures as the most common type of injury,11 26 27 it has been suggested that increased muscle temperature and the resulting increase in muscle activation may be preventative, as ACL injuries occur during the first 50 ms of early impact 25 27 28. As cold ambient temperatures are known to significantly decrease muscle temperature and the rate of force development,29 a combination of active and passive methods is recommended for athletes performing at subzero temperatures 1 8 30…”
Section: Discussionmentioning
confidence: 99%
“…Skiers are most exposed to the cold during competition when thinly dressed in race suits and thin base layers to optimize aerodynamics and obtain good freedom of movement during dynamic skiing. However, it is of course important to select the right type of material and number of base layers according to the weather conditions, balancing needs for sweat evaporation and insulation, as described by Gatterer et al 29 …”
Section: Discussionmentioning
confidence: 99%
“…Skiers are most exposed to the cold during competition when thinly dressed in race suits and thin base layers to optimize aerodynamics and obtain good freedom of movement during dynamic skiing. However, it is of course important to select the right type of material and number of base layers according to the weather conditions, balancing needs for sweat evaporation and insulation, as described by Gatterer et al 29 Unlike the competition, training sessions provide the individual a greater opportunity to make their own conscious choices on how to avoid the impact of severe cold on the body and airways. The participants described that they were usually good at adapting and changing planned training in the event of severe cold.…”
Section: Experiences Of Training and Competition In Low Temperaturesmentioning
confidence: 99%
“…39 The evidence in the literature is conflicting, with some studies stating no benefit to staying in the water longer, with a significant increase in risk as the body temperature falls. 40,41 Another study found significant changes in blood markers, and consequent theorized effects of these changes only occurred after a significant period of immersion. 42 Our data did not align with the time periods indicated in these studies (10 minutes or fewer or more than an hour), instead suggesting a period of more than 15 minutes in winter, or 30 minutes in summer, to be the most effective length of time to spend in the water with the goal of reducing mental health symptoms.…”
Section: Psychological Symptoms Caused By Menstruation and Perimenopausementioning
confidence: 99%